Factors Increasing the Investment Attractivity of The Economy - Ravzatov Jonibek Baxromovich (Periodica Journal, 2022)
This article analyzes the importance of investment attractiveness in the economy and the factors influencing it. In this analysis , the levels of investment, investor perceptions and the BERI index are considered in the process of assessing the investment climate
Keywords: process; investment; perceptions; assessing